Soil Health, Carbon Storage, and Ecosystem Service Valuation in Coffee Agroforestry Systems of Bener Meriah, Aceh - Sri Julidar; Satriawan, Halus; Ernawita; Orang Kaya Hasnanda Syahputra (Journal of Sylva Indonesiana, 2026)
Agroforestry has been promoted as a sustainable land-use model to reconcile agricultural production with ecosystem service provision. This study evaluates soil health indicators and their economic valuation in coffee agroforestry versus monoculture systems in Bener Meriah, Aceh, Indonesia. Forty soil samples were analyzed for physical, chemical, and biological parameters, including bulk density, porosity, soil organic carbon (SOC), total nitrogen (N), available phosphorus (P), and soil organisms. Results indicate that coffee agroforestry consistently improves soil physical, chemical, and biological properties compared to monoculture systems, leading to enhanced carbon storage, nutrient retention, and hydrological regulation. These improvements translate into higher indirect economic values of ecosystem services, highlighting the multifunctional benefits of agroforestry for sustainable coffee production. These findings confirm that coffee agroforestry enhances soil health, supports multiple ecosystem services, and delivers higher economic benefits than monoculture. Agroforestry thus represents a multifunctional and sustainable landscape model for coffee production in tropical regions.